2014
DOI: 10.1080/13504509.2014.880959
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous community awareness and rights to forest in Kawang Forest Reserve, Sabah, Malaysia

Abstract: This empirical study measured the community's level of awareness toward forest use rights and the socioeconomic attributes influencing the community's awareness within three villages surrounding the Kawang Forest Reserve, Sabah, Malaysia. A total of 149 respondents were selected by stratified random sampling from the selected villages. A total of 29 scale-based queries related to community awareness from eight major categories (e.g., the forest resources utilization, forest resources extraction, access to fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Malaysia is not exempted from the low participation of the local people in biosphere reserve activities. Nelson et al (2014) found a negative correlation between the characteristics. For instance, knowledge about the role of the forest to the local people in Kawang Forest Reserve, Sabah, Malaysia.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Malaysia is not exempted from the low participation of the local people in biosphere reserve activities. Nelson et al (2014) found a negative correlation between the characteristics. For instance, knowledge about the role of the forest to the local people in Kawang Forest Reserve, Sabah, Malaysia.…”
Section: Resultsmentioning
confidence: 90%
“…Amongst the major recommendations across the Asian authors is two-way communication mechanisms, development of employment opportunities, cross-sectoral participation and collaboration, implementation of locally-based management solutions and techniques to improve the biosphere reserves awareness via education. In Malaysia, Nelson et al (2014) recommended appropriate policy and organisational steps to enhance the community in the participation of community-based resources management. Also, proper training and motivation in the form of employment creation should be provided for the community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…People´s awareness can influence their attitude and participation in natural resource use and management (Arjunan et al 2006;Heinen and Shrivastava 2009;Sirivongs and Tsuchiya 2012;Tesfaye et al 2012;Nelson et al 2014). Thus, this research considers human awareness as a factor that affects forest ecosystems as well as changes people´s demand for FES.…”
Section: Local People´s Awarenessmentioning
confidence: 99%